Mumps Orchitis: Clinical Aspects and Mechanisms - Wu, Han; Wang, Fei; Tang, Dongdong; Han, Daishu (Frontiers in Immunology, 2021)
The causative agent of mumps is a single-stranded, non-segmented, negative sense RNA virus belonging to the Paramyxoviridae family. Besides the classic symptom of painfully swollen parotid salivary glands (parotitis) in mumps virus (MuV)-infected men, orchitis is the most common extra-salivary gland inflammation. Mumps orchitis frequently occurs in post-pubertal and young adult men, and leads to pain and swelling of the testis. The administration of MuV vaccines in children has been proven highly effective in reducing the incidence of mumps. However, a recent global outbreak of mumps and the high rate of orchitis is threatening male fertility. The pathogenesis of mumps orchitis remains largely unclear due to lack of systematic clinical data analysis and animal models studies. The alarming increase in the presentations of mumps orchitis and high risk of the male fertility should arise more concerns on the disease. Recent studies are revealing the mechanisms by which MuV-host cells interaction and MuV infection induces inflammatory responses in the testicular cells. In this mini-review, we highlight advances in our knowledge of the clinical aspects of mumps orchitis and possible mechanisms.